2008
DOI: 10.1590/s1516-89132008000400019
|View full text |Cite
|
Sign up to set email alerts
|

Spray-dried tomato powder: reconstitution properties and colour

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
1
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 19 publications
(12 reference statements)
7
28
1
7
Order By: Relevance
“…Other results reported in the literature do not show statistical differences under different drying conditions for this reconstitution property either (SOUSA et al, 2008;KHA;NGUYEN;ROACH, 2010). Probably the microcapsules did not show difference in this parameter because the solubility is strongly influenced by the carrier type (YOUSEFI; EMAM-DJOMEH; MOUSAVI, 2011), which was not investigated in the present study.…”
Section: Solubilitymentioning
confidence: 50%
“…Other results reported in the literature do not show statistical differences under different drying conditions for this reconstitution property either (SOUSA et al, 2008;KHA;NGUYEN;ROACH, 2010). Probably the microcapsules did not show difference in this parameter because the solubility is strongly influenced by the carrier type (YOUSEFI; EMAM-DJOMEH; MOUSAVI, 2011), which was not investigated in the present study.…”
Section: Solubilitymentioning
confidence: 50%
“…These values were higher when compared with 85.91-90.00% in spray-dried sapodilla (Chong and Wong 2015), 91.43-94.98% in spraydried amla powder (Mishra et al 2014). 17.65-26.30% in spray-dried tomato powder (Sousa et al 2008) and 36.91-38.25% in gac powder (Kha et al 2010). The high solubility observed in spray-dried honey jackfruit powder makes it suitable for reconstitution.…”
Section: Spray Drying Effect Of Inlet Temperaturementioning
confidence: 90%
“…Mishra et al (2014) and Sousa et al (2008) also observed that inlet drying temperature had no significant effect on solubility of amla and tomato powders. Solubility of honey jackfruit powder ranged from 95.79 to 98.71% in the present study.…”
Section: Spray Drying Effect Of Inlet Temperaturementioning
confidence: 95%
“…Os resultados da Tabela 3 mostram que a solubilidade do pó oriundo da pasta com 4% de lipídios apresentou maior solubilidade em água. Além disso, os valores obtidos foram superiores aos encontrados na literatura, como no pó de tomate (Sousa et al, 2008) e inferiores obtidos por polpa de frutas (Dantas, et al, 2009). A solubilidade do pó irá depender das proporções de componentes hidrossolúveis como a pectina (presente no tomate), amido (presente na batata) e concentração de açúcares.…”
Section: Resultsunclassified